Comparison of Sutureless and Conventional Laparoscopic Partial Nephrectomy: A Propensity Score-Matching Analysis - Zhang, Feng; Gao, Shuang; Zhao, Yiqiao; Wu, Bin; Chen, Xiaonan (Frontiers in Oncology, 2021)
Objective: To compare the functional outcome, safety and efficacy of sutureless and conventional laparoscopic partial nephrectomy. Methods: After the inclusion and exclusion criteria were applied, our study reviewed 379 patients with T1 stage renal tumors. We applied propensity score matching (PSM) to limit potential baseline confusion. Perioperative and functional outcomes between sutureless laparoscopic partial nephrectomy (sLPN) and conventional laparoscopic partial nephrectomy (cLPN) groups were compared and analyzed before and after PSM. Results: Of our 379 patients with T1 stage renal tumors, 199 and 180 were identified in the cLPN and sLPN groups, respectively. After applying PSM with preoperative features, 116 patients in the cLNP group were paired to 116 patients in the sLNP group. We found that all differences in preoperative baseline characteristics disappeared. All the preoperative characteristics (age, gender, tumor diameter, RENAL nephrometry score, side, preoperative eGFR, hypertension, diabetes mellitus, ASA score) were not statistically different between the two groups. The operative time(OT) (p<0.001) and warm ischemia time(WIT) (p<0.001) of the sLPN group were of shorter duration than that of the cLPN group. The eGFR baseline was almost equal, but there was a statistically smaller decrease in eGFR in the sLPN than in the cLPN group 1 week after surgery (14.3 vs 7.4, p<0.001) and after 6 months (11.9 vs 5.0, p<0.001). After both preoperative features and WIT were included in PSM, fifty-one pairs of patients were identified between the groups, the WIT difference between them disappeared, while the decrease in eGFR between the groups remained as it was previously at 1week (15.4 vs 8.6, p<0.001) and at 6 months (13.0 vs 6.2, p<0.001). Conclusion: Sutureless laparoscopic partial nephrectomy is as safe and effective as conventional laparoscopic partial nephrectomy, and compared to cLPN, sLPN can effectively reduce the WIT, retain more renal parenchyma and protect renal function.